Comparative Analysis of Antioxidative Mechanisms in Chlorella vulgaris, Isochrysis galbana, and Tetraselmis chuii Under pH Stress - Norhayati Yusuf; Nurul Shafiqa Yusof (Bogor Agricultural University, Indonesia, 2026)
Microalgae such as Chlorella vulgaris, Isochrysis galbana, and Tetraselmis chui, play a vital role in aquatic ecosystems and have considerable biotechnological applications. Medium pH strongly influences their physiological performance and oxidative balance. This study investigated the antioxidative responses of these three species grown under initial pH conditions ranging from 4 to 10, to elucidate species-specific adaptive strategies to pH-induced oxidative stress. Growth performance, enzymatic antioxidants (superoxide dismutase, SOD; catalase, CAT; guaiacol peroxidase, GPX; glutathione reductase, GR), and non-enzymatic antioxidants (ascorbate, AsA; glutathione, GSH; chlorophylls; carotenoids) were assessed. The results revealed distinct antioxidative strategies among the species. C. vulgaris relied predominantly on enzymatic defence mechanisms, showing marked upregulation of SOD, GPX, and GR. Compared with control conditions, SOD and GPX activities increased by 40.7% and 17.1%, respectively, at pH 4, while GR activity increased by 42.8% at pH 10. In contrast, I. galbana exhibited a more selective response, with strong induction of CAT activity (29.9%) at pH 4 and a substantial increase in total GSH content (79%) at pH 7, while APX activity was highest under control pH conditions. T. chuii demonstrated a balanced antioxidative strategy, combining moderate enhancement of enzymatic activity, particularly GR (17.2%) at pH 7, with pronounced accumulation of non-enzymatic antioxidants, including carotenoids (60.9%) and GSH (42.4%). These findings highlight the diverse adaptive capacities of microalgae to pH stress and provide valuable insights for optimising microalgal cultivation in biofuel production, aquaculture, and environmental management, as well as for developing stress-tolerant strains for sustainable biotechnological applications.